Respiratory Epithelial Adenomatoid Hamartomas: An Increasingly Common Diagnosis in the Setting of Nasal Polyps. Issue 4 (July 2016) - Davison, Wesley L.; Pearlman, Aaron N.; Donatelli, Luke A.; Conley, Lindsey M.
Background: Respiratory epithelial adenomatoid hamartomas (REAH) are benign nose neoplasms found in the nasal cavity and sinuses. Symptoms include anosmia, nasal obstruction, facial pressure, and rhinorrhea. Although previously thought to be rare, these tumors are being increasingly recognized on pathology in patients undergoing endoscopic sinus surgery. However, REAH is difficult to diagnose before surgery because it may mimic other entities, such as nasal polyps or inverted papilloma, and is often found incidentally only after surgery. Objective: The aims of this study were to (1) add an additional case series of REAH to the literature, (2) report unique imaging findings on computed tomography and magnetic resonance imaging, and (3) pool and summarize all available data from existing publications. Methods: Retrospective chart review from years 2004 to 2015 and a literature review Results: Twenty-three cases were found in our case series, which included 12 men (52%) and 11 women (48%), with a mean age of 59 years. No cases were found before 2007. Lund-Mackay scores were comparable with those found in chronic rhinosinusitis without nasal polyposis. Imaging consistently demonstrated a discoid-shaped mass at the olfactory cleft. Fifty previous publications were found (4 prospective, 11 retrospective studies, 9 case series, 26 cases reports), which included 660 patients diagnosed with REAH. Pooled data revealed a mean age of 54 years (range, 9–86 years) and a male to female ratio of 3:2. Conclusion: The results of our study further refined the average age at which REAH diagnosis occurs as 54 years old, although it may occur at any age. There is a clear male-to-female predominance (3:2). In addition, olfactory cleft widening and discoid soft tissue at the olfactory cleft are hallmark radiographic findings. The vast majority of published cases occurred during the past 4 years, which indicated increased recognition of REAH.